Role of companies' size in socio-economic development of regions in the Czech Republic - Redlichová, Radka (Array, 2019)
The aim of this paper is to investigate socio-economic development drivers of NUTS 3 regions in the Czech Republic. The aim is fulfilled by examination of the relationship between one of the regional development factors – the companies’ size structure and the development of the region from both socio and economic views. We derive from the theory of diversification and prior empirical findings, and empirically test the role of companies’ size in regional development. We use a balanced dataset of 14 regions covering the years 2000 – 2016 that provides the information about regions’ socio-economic performance in terms of GDP and unemployment rate. We hypothesise that unemployment rate in the regions with higher share of small firms is less sensitive to the general trend of the whole economy. However, the higher share of small firms leads to improved regional GDP. Our findings confirm that small firms accelerate economic growth while playing a role of a social stabiliser in Czech regions. Our conclusions could help in designing the regional policy in the Czech Republic.